(untitled) (Colombia Medica, 2015)
Objective: To evaluate the impact of a strategy for early detection of diabetic retinopathy in patients with type 2 diabetes mellitus (DMT2) in Quintana Roo, México. Methods: Study transversal, observational, prospective, analytical, eight primary care units from Mexican Social Security Institute in the northern delegation of the State of Quintana Roo, Mexico were included. A program for early detection of diabetic retinopathy (DR) in adult 376,169 was designed. Were diagnosed 683 cases of type 2 diabetes, in 105 patients randomized was conducted to direct ophthalmoscopy were subjected to a secondary hospital were assigned. Will determine the degree of diabetic retinopathy and macular edema was performed. Results: In population were 55.2% female, mean age 48+11.1 years, 23.8 % had some degree of DR, 28.0% with mild non- proliferative diabetic retinopathy 48.0 % moderate 16.0% and severe and 8.0% showed proliferative diabetic retinopathy. Those over age 30 are 2.8 times more risk of developing DR, OR= 2.8; 95%CI: 0.42-18.0, and OR= 1.7; 95%CI: 1.02-2.95 women. Conclusions: The implementation of programs aimed at the early detection of debilitating conditions such as diabetic retinopathy health impacts beneficiaries, effective links between primary care systems, and provide second level positive health outcomes for patient diseases.